Dyslipidemia, atherosclerosis and cardiovascular disease: an increasingly important triad in an aging population living with HIV. (October 2013) - O'Halloran, Jane A; Satchell, Claudette S; Mallon, Patrick WG
As a result of major advances in the management of HIV over the last two decades, patients living with HIV are now encountering comorbidities commonly associated with aging. Cardiovascular disease is the leading cause of death worldwide. As the population living with HIV ages, understanding cardiovascular disease in the setting of HIV is of increasing importance. This review examines the complex interplay between cardiovascular disease, HIV infection and the drugs used to treat it, with particular emphasis on the contribution of dyslipidemia.